Pleuropulmonary blastoma – primary malignant lung tumor in children - Tejza, Barbara (Pediatria Polska - Polish Journal of Paediatrics, 2025)
Pleuropulmonary blastoma (PPB) is a primary, malignant tumor in children up to 6 years of age. It is a rare tumor and may cause diagnostic difficulties. A 3-year-old girl was hospitalized due to pneumonia and dyspnea. Based on the symptoms, laboratory tests and computed tomography images, inflammatory changes were suspected to be caused by a congenital lung defect. There was no improvement after conservative treatment, so the decayed basal segments of the left lower lobe were removed by thoracotomy. Histopathological examination confirmed PPB type III with the DICER1 mutation. The girl underwent postoperative chemotherapy. There were no signs of progression after treatment. Pleuropulmonary blastoma is a malignant tumor and requires combined oncological treatment. The prognosis depends on the histological type and radical tumor resection. Testing for the DICER1 mutation is helpful in the diagnosis of solid-cystic lung lesions in children.